Fortalecimiento turístico al Plan de Desarrollo y Ordenamiento Territorial (PDyOT) del cantón Olmedo, provincia de Loja - Jimenez Ojeda, Johanna Lizbeth (2020)
The present research work named "Strengthening tourism to the Development and Territorial Ordering Plan (PDyOT) of the Canton Olmedo, province of Loja" has been proposed as an alternative for the development of the tourist activity within the Canton, with the main participation of the actors involved in tourism. The general objective of the research is to "Strengthen the Development and Territorial Ordering Plan (PDyOT) of the Olmedo Canton, Loja Province", and three specific objectives: Carry out a diagnosis of the tourism component of the Olmedo Canton, Elaborate a proposal for the development of tourism in the Olmedo Canton and Generate the general guidelines of the three main strategies proposed in the proposal for the development of tourism in the Olmedo Canton. To meet the first specific objective, the pertinent information was generated through primary and secondary documentary sources, which also consti tute valid sources of information such as: PDyOT de Olmedo, Tourist Diagnostic of the Cant Olmedo 2019, other theses and research documents, in addition to use the methodology for ranking tourist attractions of MINTUR 2018, by means of which the main tourist attractions of the canton were determined and analyzed, in addition to verifying that the characteristics that they possess are those necessary to generate tourist products, this information was also validated with visits in situ, obtaining the following results: 11% of attractions are natural and 89% cultural, all in Hierarchy II, it was also determined that the products with the highest production are Coffee and those derived from sugarcane, likewise it was identified that the infrastructure and tourist plant are limited. For the fulfillment of the second specific objective a SWOT matrix was applied through a participatory workshop with a focus group of actors involved in Tourism, in which the aspects that benefit and harm the development of tourism in Olmedo were known, based on the information generated, several tourist strategies were proposed that through a Likert scale applied to the same group, the three most valued strategies were determined according to their criteria and experience in the development of the tourist environment, first of all: the implementation of a program or tour package taking advantage the resources of the Canton, as a second strategy: the design of a tourist booklet with the tourist offer that is held and as a third strategy: the approach of trainings to be given to tourist staff in the Canton, which were designed under a vision of tourism development, where coffee and sugarcane derivatives, such as artisanal sweets, stand out as productive potentiality. For the third specific objective, a tour package proposal was designed "Tourism and Culture Route", a two-day, one-night program. In addition, a tourist booklet was designed, including the most relevant tourist information of the Canton, and finally, in order to establish the general guidelines for the training courses, themes were proposed based on the information generated in the research, which were then ranked in the territory to 4 determine the most valued ones by means of a Likert scale applied to the actors involved in tourism in the Canton, resulting in training courses: Enterprises, Customer Service and Food Security, therefore a technical tab was proposed for each training. These will contribute to the improvement of tourism and production of the population. As for the recommendations, they are addressed to the Decentralized Autonomous Government (GAD) of Olmedo for the regularization of the services provided by the tourist plant, to the Tourism Unit for the updating of tourist data land register and also for the implementation of the proposal based on the strategies developed for the Development and Territorial Ordering Plan, and finally to the population to train within the tourist field.